2014
DOI: 10.1016/j.amepre.2013.11.016
|View full text |Cite
|
Sign up to set email alerts
|

Breast and Cervical Screening by Race/Ethnicity

Abstract: Background Traditionally, economic recessions have resulted in decreased utilization of preventive health services. Purpose To explore racial and ethnic differences in breast and cervical cancer screening rates before and during the Great Recession. Methods The Medical Expenditure Panel was the source for identifying 10,894 women, ages 50–74 for breast screening and 19,957 women, ages 21–65 for cervical screening. Survey years included 2004-2005 and 2009-2010. Dependent variables were as follows: 1) receip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…These results are consistent with other studies examining cancer screening trends in the U.S. A recent study observed that breast cancer screening decreased in the recession, a trend attributed to a decline in insurance coverage caused by the recession, predominantly among White women ( King et al, 2014 ). Contrary to our results, one study examining colorectal cancer screening, before and during the recession, observed that those with insurance reported significant declines in colonoscopy screening during the recession.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results are consistent with other studies examining cancer screening trends in the U.S. A recent study observed that breast cancer screening decreased in the recession, a trend attributed to a decline in insurance coverage caused by the recession, predominantly among White women ( King et al, 2014 ). Contrary to our results, one study examining colorectal cancer screening, before and during the recession, observed that those with insurance reported significant declines in colonoscopy screening during the recession.…”
Section: Discussionsupporting
confidence: 92%
“…For instance, King et al observed that mammography screening was higher among Black participants in comparison to Whites before and during the recession. They postulated that this may be due to less severe income reductions for Blacks, and/or a higher percentage of Blacks qualifying for public insurance ( King et al, 2014 ). Alternatively, Akinyemiju et al reported that screening rates were actually higher for White participants compared Black participants after adjusting for misclassification in self-reported screening rates ( Akinyemiju et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have examined the impact of Medicaid expansion on self-reported breast cancer screening among US adults. 3,26,33-40 Similar to our findings, other studies have observed significant reductions in breast cancer screening in the post-expansion period. 26,34-36,39 Two US studies 26,36 found a 13% 26 and 20% 36 reduced odds of breast cancer screening in the post-expansion period among women aged 50 to 74 years.…”
Section: Discussionsupporting
confidence: 90%
“…Future studies are needed to better target these disparate populations and address barriers to health-care access. Fourth, while self-reported measures of women’s cancer screening in the BRFSS have been validated 47,48 as we and others have shown that 34-37,39 self-reported measures of breast cancer screening are subject to recall bias 49 resulting in misclassification, with a significant proportion of participants overreporting screening practices. Data using objective measures of screening from claims data across Medicaid expansion and Appalachia states may be necessary to definitively estimate the impact of the ACA on breast cancer screening in the United States.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation